Intended Near‐Total Removal of Koos Grade IV Vestibular Schwannomas: Reconsidering the Treatment Paradigm. Issue 2 (February 2018) - Zumofen, Daniel Walter; Guffi, Tommaso; Epple, Christian; Westermann, Birgit; Krähenbühl, Anna‐Katharina; Zabka, Susanne; Taub, Ethan; Bodmer, Daniel; Mariani, Luigi
Abstract : BACKGROUND : The goals of treating Koos grade IV vestibular schwannomas are to relieve brainstem compression, preserve or restore neurological function, and achieve long‐term tumor control while minimizing tumor‐ and treatment‐related morbidity. OBJECTIVE : To propose a treatment paradigm involving the intentional near‐total removal of Koos grade IV vestibular schwannomas, in which a small amount of residual tumor is not dissected off the cisternal portion of the facial nerve. Patients are then followed by a wait‐and‐scan approach. Any subsequent volumetric progression of the residual tumor is treated with radiosurgery. METHODS : This is a case series of 44 consecutive unselected patients who underwent intended near‐total resection of a Koos grade IV vestibular schwannoma through a retrosigmoid approach from January 2009 to December 2015. Pre‐ and postoperative volumetric analyses were performed on routine magnetic resonance imaging sequences (constructive interference in steady state and gadolinium‐enhanced T1‐weighted sequence). RESULTS : The mean preoperative tumor volume was 10.9 cm 3 . The mean extent of resection was 89%. At the last clinical follow‐up, facial nerve function was good [House and Brackmann (HB) I‐II] in 89%, fair (HB III) in 9%, and poor (HB IV‐VI) in 2% of the patients. At the last radiological follow‐up, the residual tumor had become smaller or remained the same size in 84% of patients. Volumetric progression was negatively correlated with the original extent of resection and positively correlated with postoperative residual tumor volume ( P = .01, P < .001, respectively). CONCLUSION : Intended near‐total removal results in excellent preservation of facial nerve function and has a low recurrence rate. Any progressive residual tumor may be treated by radiosurgery.